THE CORRELATION BETWEEN WRITING SELF-PERCEPTION AND WRITING SKILL AT THE TENTH GRADE STUDENTS OF SMA INTEGRAL HIDAYATULLAH BATAM IN THE ACADEMIC YEARS 2020/2021 - Rahma, Feby Fatika; Dewi, Desi Surlitasari; Wilany, Eka (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
The aim of this study was to find out whether there is a correlation between students' writing self-perception and students' writing skill. The research design used in this research was quantitative correlational research. The populations in this study were 25 students of tenth grade students of SMA Integral Hidayatullah Batam in academic years 2020/2021. The population was selected by using cluster random sampling technique. The sample in this research was 14 students. Writing Self-Perception Scale (WSPS) and Writing Test were used as instruments of this study after the validity and reliability tests of the two instruments were conducted. The data normality test used in this study was Saphiro Wilk. The researcher analyzed the correlation using the Pearson Product Moment formula to find out correlation between Students’ Writing Self-Perception and Students’ Writing Skill at tenth grade students of SMA Integral Hidayatullah Batam in academic years 2020/2021. The research found out that there was a significant correlation between Students' Writing Self-Perception and Students' Writing Skill at tenth grade students of SMA Integral Hidayatullah Batam in the Academic Year 2020/2021. Suggestions were taken by researcher, namely that teachers can find writing activities to support the students to have a positive writing self-perception.